2014
DOI: 10.1590/1809-4503201400050008
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in Brazilian school children: analysis of the National Adolescent School-based Health Survey (PeNSE 2012)

Abstract: ABSTRACT:Objective: To describe the victimization and bullying practice in Brazilian school children, according to data from the National Adolescent School-based Health Survey and to compare the surveys from 2009 and 2012. Methods: This is a cross-sectional study with univariate and multivariate analyzes of the following variables: to have been treated badly by colleagues, to have been bullied and to have bullied other children. The following independent variables were analyzed: age, sex, race/color, type of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 20 publications
4
49
1
9
Order By: Relevance
“…In Brazil, the first two PeNSEs (National School Health Survey) found increasing rates of involvement in bullying among the students; 5.4% of students in state capitals reported having been bullied in 2009, and 7.2% in 2012 [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the first two PeNSEs (National School Health Survey) found increasing rates of involvement in bullying among the students; 5.4% of students in state capitals reported having been bullied in 2009, and 7.2% in 2012 [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…A avaliação de uma amostra de 109.104 escolares brasileiros com desenvolvimento típico indicou que 27,5% dos participantes relatou não ser bem tratados pelos colegas e 7,2% reportou sofrer bullying (MALTA et al, 2014). Se em populações com desenvolvimento típico os dados de prevalência de bullying já são preocupantes, quando se aborda a reação dos pares frente aos colegas com deficiência tais estatísticas são alarmantes, um vez que, quando comparados a alunos que não apresentam deficiência, crianças com algum tipo de deficiência estão em maior risco de sofrer bullying e rejeição pelos colegas de classe (ROSE; MONDA-AMAYA; ESPELAGE, 2011).…”
Section: Santa Mariaunclassified
“…[4][5][6] The acts of aggression that comprise bullying are classified into three main groups: physical, such as hitting, kicking and using weapons to attack; verbal/psychological, which includes threats, insults, tricks, nicknames and humiliation; and indirect, represented by behaviors of social exclusion, indifference and extortion. [7][8][9] There is also the form called cyber-bullying, which covers repeated aggression with intent to persecute and humiliate, through electronic devices, especially cell phones and the internet.…”
Section: Introductionmentioning
confidence: 99%
“…2 In Brazil, the National Survey of School Health (PENSE) of 2012 revealed that suffering bullying by a colleague affected 7.2% of schoolchildren, while 20.8% of students showed some kind of bullying against schoolmates. 8 When analyzing the international scientific production on the subject, there were obstacles in the conceptualization and operationalization of the term bullying, as well as in the translation itself. In addition to conceptual differences, another aspect that generates disagreement is the definition of a cut-off point for bullying, that is, the minimum frequency capable of transforming a violent school event into bullying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation